2018
DOI: 10.1007/s10533-018-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

How do chronic nutrient loading and the duration of nutrient pulses affect nutrient uptake in headwater streams?

Abstract: Our study aimed to analyze the effects of chronic nutrient loading on the capacity of headwater streams to retain phosphorus and ammonium pulses of different duration. For this purpose, we selected nine headwater streams located across a gradient of increasing agricultural land use and eutrophication. In each stream, we performed sequential plateau additions with increasing nutrient concentrations in summer 2015 and instantaneous slug additions in summer 2016 under similar hydrological conditions. We modelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…For example, EPC 0 can change following storm events or changes in sediment sources due to new sediments depositing on the streambed (Emelko et al., 2016; McDowell et al., 2019). Excessive DRP loading could overwhelm the capacity of the sediment P buffer, weakening the P uptake potential in the stream (Marti et al., 2004; Meyer, 1979; Weigelhofer et al., 2018b). In a way, sediment EPC 0 integrates past biogeochemical changes in the stream network, including the history of sediment exposure to DRP (Hamilton, 2012; Jarvie et al., 2005), which may influence current, in‐stream P cycling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, EPC 0 can change following storm events or changes in sediment sources due to new sediments depositing on the streambed (Emelko et al., 2016; McDowell et al., 2019). Excessive DRP loading could overwhelm the capacity of the sediment P buffer, weakening the P uptake potential in the stream (Marti et al., 2004; Meyer, 1979; Weigelhofer et al., 2018b). In a way, sediment EPC 0 integrates past biogeochemical changes in the stream network, including the history of sediment exposure to DRP (Hamilton, 2012; Jarvie et al., 2005), which may influence current, in‐stream P cycling.…”
Section: Introductionmentioning
confidence: 99%
“…We then should conclude that our streams did not experience saturation during the enrichments. Likewise, a significant number of studies conducting both plateau and slug additions reported uptake curves (i.e., U-C) deviating from M-M saturation models or reflecting only the linear "unsaturated" range of the M-M curve (e.g., Dodds et al, 2002;O'Brien et al, 2007;Trentman et al, 2015;Weigelhofer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of pulses additions can also take advantage of the entire range of concentrations observed during the enrichment to estimate nutrient uptake. Determining nutrient retention under multiple enrichment levels is particularly important to systems exposed to variable loads (Weigelhofer et al, 2018), where nutrient uptake is likely to be controlled by the biofilm kinetics (Dodds et al, 2002). Moreover, slug additions can be used to estimate nutrient uptake during nonsteady-state hydrological conditions (Ribot et al, 2019;Runkel et al, 1998;Wollheim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The EPC 0 is a common tool to assess P sorption interactions between sediments and the water column in streams, as it estimates the phosphorus buffering capacity of benthic sediments [44,69]. EPC 0 is sensitive to hydrological events [37,44], fresh sediment inputs [70,71], and excessive SRP loads due to point source and diffuse pollution [70]. Furthermore, EPC 0 can incorporate information on past biogeochemical changes in the stream network, affecting in-stream P cycling [44].…”
Section: Effects Of the Two-stage Ditch And The Floodplain On Sediment Processesmentioning
confidence: 99%